2015
DOI: 10.1016/j.wocn.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing respiratory contributions to f0 declination in German across varying speech tasks and respiratory demands

Abstract: Many past studies have sought to determine the factors that affect f0 declination, and the physiological underpinnings of the phenomenon. This study assessed the relation between respiration and f0 declination by means of simultaneous acoustic and respiratory recordings from read and spontaneous speech from speakers of German. Within the respective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Concerning the cognitive‐linguistic demand manipulation, our results on the effects of phonological length on the duration of the pause before the Object constituent and on pitch declination slope are in line with previous studies on healthy individuals (Cooper & Sorensen, ; Fuchs et al ., , ; t'Hart, ; Thorsen, ), further supporting that the temporal and melodic characteristics of speech are indicative of speech production planning. Specifically, we found that the duration of the pause before the Object constituent (pause‐O) was longer before long constituents and shorter before short constituents.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Concerning the cognitive‐linguistic demand manipulation, our results on the effects of phonological length on the duration of the pause before the Object constituent and on pitch declination slope are in line with previous studies on healthy individuals (Cooper & Sorensen, ; Fuchs et al ., , ; t'Hart, ; Thorsen, ), further supporting that the temporal and melodic characteristics of speech are indicative of speech production planning. Specifically, we found that the duration of the pause before the Object constituent (pause‐O) was longer before long constituents and shorter before short constituents.…”
Section: Discussionmentioning
confidence: 77%
“…That is, they know in advance how long their utterance is going to be and they will thus systematically plan pitch declination in advance. The slope of pitch declination across an utterance is steeper for shorter utterances and shallower for longer utterances (Cooper & Sorensen, ; Fuchs et al ., ; Fuchs, Petrone, Rochet‐Capellan, Reichel, & Koenig, ). A schematization of the findings on healthy speakers for pause duration and pitch declination is illustrated in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, a few other factors seem to be relevant here. First, research has indicated that prepared speech generally involves more anticipatory speech planning (e.g., Fuchs, et al, 2015), and in this way, when speakers read from a script, there is more in-advance processing at work, which could lead to more declination. Therefore, this could be one of the reasons for the smaller amount of declination in these spontaneous declaratives.…”
Section: Flatter Contoursmentioning
confidence: 99%
“…RST is used in the diagnosis of the sleepless syndrome, and its purpose is to know if the upper body is inflamed by examining the signals of a patient's respiration. The two RST have been used previously in examining the differences in speech rhythm ( [7], [8]), the correlation between pitch and intensity ( [9]), gender differences ( [10]), the F0 declination ( [11]), and turn-taking in dialogue ( [12]), among other uses.…”
Section: Introductionmentioning
confidence: 99%